TRADISI JAMU LAUT DALAM PERSPEKTIF SOSIO EKONOMI PADA MASYARAKAT PANTAI CERMIN KABUPATEN SERDANG BEDAGAI - Yusrizal Yusrizal; Nikmaturridha Nikmaturridha; Khairuddin Khairuddin (Universitas Islam Negeri Sumatera Utara, 2015)
Implementation of the tradition of “Jamu Laut” is one of the marine community tradition that persists to this day. The tradition of the “Jamu Laut” can provide understanding and patterns of behavior in a fishing community to interact with the natural environment and social environment to form social values high presented of symbolic rituals. Then “Jamu Laut” tradition also by the implementation of the sea gives a pattern of ritual and piety servant to the creator who has given the gift of sustenance and livelihood for the fishermen in the social perspective it appears that the implementation of traditions “Jamu Laut” provide a sense of mutual cooperation and also have respect for the sea and the handler too religious figures emerging from the sea Ralung symbol, while the economic perspective seen that the implementation of the tradition of JamuLautcan increase the income of fishermen due to the high level of enthusiasm to be able to catch fish and also with ceremonial event conducted to provide an increase in purchasing power of economic activities such as souvenir trade, rental, rent tent, opened the restaurant and also other economic activities that have an impact on consumer purchasing power and also has implications for the pattern of household consumption fishermen.